« Anywhere out of this room » : les poèmes énigmatiques des poétesses victoriennes - Fabienne Moine (Cahiers Victoriens et Edouardiens)
Victorian women poets, along with certain Pre-Modernist ones (from Elizabeth Barrett Browning, Laetitia Landon or Christina Rossetti to other, less well-known ones today, such as Dora Greenwell or Adelaide Procter), have written some disturbing and informal poems that do not always meet accepted Victorian generic or thematic standards. As the reader peruses these poems, he/she feels strangely close to them since he/she is invited to share the enigma or secret that will remain concealed, provoking further frustration. Revelation is perpetually postponed to another space, strange and boundless as well as foreign, whose language the reader will have difficulty coming to terms with. This space therefore points towards another poetical, forever indeterminate, territory.